DOCKING MOLEKUL DENGAN METODA MOLEGRO VIRTUAL DOCKER DARI EKSTRAK AIR Psidium guajava, Linn DAN Citrus sinensis, Peels SEBAGAI INHIBITOR PADA TIROSINASE UNTUK PEMUTIH KULIT - Ayik Rosita Puspaningtyas (Research Center for Chemistry - LIPI, 2013)
We have been molecular docking using MolegroVirtual Docker (MVD) on water extract of guava fruit(Psidiumguajava, Linn) and sweet orange (Citrussinensis,Peels) as inhibitor on enzyme tyrosinase withascorbic acid (vitamin C) as positive control to studywhitening agent. Based on the previous studies, the maincontent of the water extract of guava fruit (Psidiumguajava)are 2,6-dihydroxy-3,5-dimethyl-4-0–D-glucopyranosilbenzophenone, 3-hydroxy-2-butanone, and vitamin C, whilethe extract juice of sweet oranges (Citrus sinensis) arelimonene, linalol, and vitamin C. In this study the resultsshowed that the main content of the water extract of Psidiumguajava fruit have better bond as inhibitor on tyrosinase thanCitrus sinensis and vitamin C which can be seen fromMoldock score of Psidiumguajava (-107.806) and Citrussinensis (-76,9593); it meanslower the energyand morestable binding. The IC50 on water extract of guava fruit(psidiumguajava) and sweet orange (Citrus sinensis) were0.26 mM and 31.07 mM, respectively. The hydrogen bonds of2, 6-dihydroxy-3, 5-dimethyl-4-0–D- glucopyranosilbenzophenone with 5amino acid of tyrosinase were Gly 200,Pro 201 , Gly 196, Phe 197, and Asn 205, while limonen,linalool binding 3 amino acids were Gly 200, Phe 197, andAsn 205. Finally, 3D MVD visualization between maincontent of guava and sweet orange water extract can beconcluded that interaction of guava fruit (psidiumguajava)water extract against tyrosinase was more harmonious andstabil than vitamin C and main content of sweet orange(Citrus sinensis) water extract.Keywords: Psidium guajava, Citrus sinensis, tyrosinase, vitamin Cand docking molecule